Juridical Analysis of the Performance of Correctional Institution Apparatuses in Fulfilling Human Rights (HAM) of Prison-Assisted Prisoners in Correctional Institutions - Mujahidin; Muammar Arafat Yusmad (LEGAL BRIEF, 2022)
The purpose of this research is to describe the performance analysis of the Class IIA Palopo Correctional Institution Apparatus in fostering the Correctional inmates. This research is a descriptive qualitative research that uses a historical approach. Sources of data in the study came from interviews and field observations, while the interviewees were the Head of Correctional Institutions, Officers, Correctional Inmates, and Nurses, while secondary data were taken from documents related to the research. The results showed that 1) The Performance System of Class II A Palopo Prison Apparatus was good because they were very responsible for their work. However, the shortage of prison officers is a bit burdensome, especially female officers who need to be added to personnel. The first coaching given is spiritual development through religion, which includes lectures, as well as self-reliance development through skills, which include sewing skills. 2) The obstacles faced in prisons are the lack of facilities for skills development programs, the low level of education of the inmates, and the lack of understanding of employees as coaches, especially in the area of ??salon/babershop skills. 3) Implementation of the fulfillment of prisoners' rights to health services at the Class II A Penitentiary of Palopo City which researchers obtained from observations and interviews from Class II A nurses of Palopo City include; 1) Promotive Services, 2) Preventive Services, 3) Curative Health Services, 4) Rehabilitative Health Services.